Understanding the concept of Khiyar (Option) among Muamalat students in ACIS UiTM Puncak Alam / Mashitah Al-Bakir Abdul Rahim. - Abdul Rahim, Mashitah Al-Bakir (2019)
Khiyar is an alternative principle in Muamalat's Islamic Law that made it possible to protect the interests of related parties in transactions. Khiyar rights are described in detail in the fiqh transaction books, particularly on trade issues. It is important to be known by people because it about right while transaction. However, many people do not know the exactly what is Khiyar about and if they face fraud while transaction, they do not know how to act. This research aim is to study the understanding level of Khiyar among Muamalat students in UITM Puncak Alam. This research include recommendations on cultivate awareness on the importance of Khiyar. Qualitative and quantitative method are use in this research which is library research and survey research (questionnaire). It is important to ensure that the concept of Khiyar is implemented by people in their contract.